Analisis Kepuasan Pelanggan Batik Benang Bintik di Kota Palangka Raya - Wenny Indriastuti; Meitiana; Bambang Mantikei (Program Pascasarjana Universitas Palangka Raya dan (and) Ikatan Ahli Teknik Penyehatan dan Teknik Lingkungan Indonesia (IATPI), 2020)
This research aims to determine the level of customer satisfaction of Batik Benang Bintik in Palangka Raya. This re-search is a quantitative research with field survey techniques. The subjects of the research are 75 customers of Batik Benang Bintik in Palangka Raya with different age and backgrounds. The data were collected through interview and questionnaire instrument which is consist of 15 questions that have previously tested for its validity and reliability. The costumers’ satisfaction were analysed in term of costumer service, promotion, price and shop location in the city. We do hope this research may provide insight to business owner and local government in their effort to enhace the poten-tial market of Batik Benang Bintik, especially in Palangka Raya city.